Annexin A11 gene polymorphism (R230C variant) and sarcoidosis in a Portuguese population. Issue 3 (19th August 2013) - Morais, A.; Lima, B.; Peixoto, M.; Melo, N.; Alves, H.; Marques, J. A.; Delgado, L.
Abstract A recent genome‐wide association study detected a protective effect for the annexin A11 rs1049550*T allele (R230Cvariant) in susceptibility to sarcoidosis. We evaluated the association between rs1049550 C/T and sarcoidosis susceptibility, distinct disease phenotypes and evolution in a Portuguese population. We performed a case–control study of 208 patients and 197 healthy controls. Samples were genotyped for rs1049550 C/T using real‐time polymerase chain reaction. The frequency of the annexin A11 rs1049550*T allele was significantly lower in patients than in controls (33.2 vs 44.9%, P < 0.001). Odds ratio of 0.52 and 0.44 were obtained, respectively for carriers of one (CT) and two (TT) copies normalized to the CC wild‐type genotype (P < 0.001). There were no significant differences in patients with and without Löfgren syndrome. A significant increase in the frequency of the T allele was observed in patients with bronchoalveolar lavage (BAL) fluid neutrophilia (P = 0.04). No significant associations were seen for lung function pattern, radiological stages or different forms of disease evolution. Our study confirms that rs1049550*T allele exerts a significant protective effect on sarcoidosis susceptibility. Given the role of annexin A11 in cell division, apoptosis and neutrophil function, this polymorphism may affect key elements of granulomatous and interstitial inflammation in sarcoidosis.